PENGARUH PERTUMBUHAN LABA, PERTUMBUHAN ARUS KAS OPERASI, PERTUMBUHAN ARUS KAS INVESTASI DAN PERTUMBUHAN ARUS KAS PENDANAAN TERHADAP PERTUMBUHAN HARGA SAHAM PADA PERUSAHAAN YANG TERCATAT DALAM INDEKS SRI-KEHATI TAHUN 2012-2015 - Ayuli Nurhusni; Lintas M. Parlindungan; Sofia Maulida; Rudy Tanjung (Jurnal Ekonomi Bisnis Indonesia, 2022)
The purpose of this study is to determine the analysis of preferences, perceptions, and behavior of TVone employees to sharia banking. Based on the variables studied then this research type is survey research with descriptive approach, quantitative. The data used are primary and secondary data with data collection techniques through the distribution of questionnaires and literature study. The research method used multiple linear regression, where the research is done by taking samples from a population. The population of this research is employees of PT Lativi Media Karya. Sampling technique using probability sampling technique with Simple Random Sampling method. The results showed that the three independent variables of only employee behavior that have significant effect on sharia banking in terms of products and sharia principles. Meanwhile, it is known that R value of 0.429 indicates that the value describes the moderate level of relationship between the variables of preference, perception and behavior toward sharia banking. As for the coefficient of determination seen from the figure on Adjusted R Square of 0.116, it shows that the percentage of contribution of independent variables of preference, perception and behavior can contribute influence of 11.6% to the dependent variable of syariah banking, and the remaining 88.4% influenced by other variables not included in this research model.